‘Ray Ruby’ grapefruit affected by huanglongbing II. Planting density, soil, and foliar nutrient management - Phuyal, Dinesh; Nogueira, Thiago Assis Rodrigues [UNESP]; Jani, Arun D.; Kadyampakeni, Davie M.; Morgan, Kelly T.; Ferrarezi, Rhuanito Soranz (American Society for Horticultural Science, 2020)
Since the arrival of Huanglongbing (HLB) disease in Florida, several management approaches, including modification of orchard architecture design and nutritional therapy, have been explored. High-density plantings anticipate early economic returns from HLB-affected orchards. With no cure available for HLB, balanced nutrient application through soil and foliar spraying can mitigate the disease. A 2-year study was conducted to investigate the effects of three grapefruit (Citrus paradisi) planting densities [single-row (300 and 440 trees per ha), and double-row high-density (975 trees per ha)], two controlled-release fertilizer (CRF) blends, and foliar-applied micronutrients (FAM) (a blend of B, Mn, and Zn at 0, 1.5, 3, and 6 times the recommended rates) on grapefruit growth and fruit yield, physiological parameters, and foliar nutrient concentrations in an HLB-affected orchard. All the trees tested positive for HLB based on real-time quantitative polymerase chain reaction (qPCR) test. The highest planting density resulted in the lowest trunk diameter and canopy volume. Despite lower yield per tree in 2019–20, 975 trees per ha planting induced the greatest fruit and solid yields per ha. Also, the fruit produced from 975 trees per ha planting tended to be acidic with the deposition of more soluble solids. Use of CRF with higher micronutrients increased canopy volume with the expense of reduced fruit number in 2019–20. FAM did not affect cycle threshold (Ct) value and tree growth parameters. Fruit yield, photosynthesis rate, and stomatal conductance (gS) decreased, and all leaf nutrient concentrations except B increased in 2019–20 with all FAM rates tested. In conclusion, our study showed that high-density planting optimizes yield under HLB-endemic conditions. In addition, supplemental soil and foliar micronutrient application do not enhance yield of HLB-affected trees over a 2-year timeframe, warranting further research for confirmation of results.